Outcome of Dorsal Onlay Urethroplasty for Long Segment Anterior Urethral Stricture: Experience of 31 Cases (Bangladesh Journal of Urology, 2020)
Objective: To determine the short-term outcome of dorsolateral onlay urethroplasty in the treatment of long segment anterior urethral stricture.Materials and Methods: A prospective study from May 2011 to September 2012 is carried out in department of Urology, National Institute of Kidney Diseases and Urology, Sher-EBanglanagar, Dhaka. Thirty one patients with long anterior urethral stricture were treated by a dorsolateral onlay buccal mucosa graft. After voiding trial, they were followed up at 3 weeks and 3 months with history, physical examination, uroflowmetry and retrograde urethrogram (RGU) if required (uroflowmetry